The prevalence of radiographic sacroiliitis in patients affected by inflammatory bowel disease with inflammatory low back pain - M. Podswiadek; L. Punzi; R. Stramare; R. D'Incà; A. Ferronato; A. Lo Nigro; G.C. Sturniolo (PAGEPress Publications, 2004)
Inflammatory bowel diseases (IBD), are Crohn's disease (CD) or ulcerative colitis (UC), are frequently complicated by joint complaints with prevalence that varies between 10 and 28 %. The IBD related arthropathy may be expressed as peripheral arthritis or axial one frequently indistinguishable from the classical ankylosing spondylitis (AS). According to ESSG criteria for spondyloarthropathy, the presence of synovitis or the inflammatory back pain (IBP) in IBD patients is diagnostic for spondyloarthropathy, but for diagnosis of as also radiological criteria must be fulfilled. There are few studies regarding the radiological prevalence of sacroiliitis in patients with IBD. We examined, by plain film radiograms of pelvis, 100 sacroiliac joints (SJ) of 50 IBD patients with IBP. The New York (1984) SJ radiological score with gradation from 0 to 4 was applied. Total sacroiliac score (SJS) was summarized between left and right side (from 0 to 8). Fourteen patients fulfilled New York modified criteria for AS and 8 patients had unilateral 2nd grade sacroiliitis. Only 4 of 14 AS patients (28%) were HLA B27 positive. Thirty patients had localized IBP, 10 extended to buttock and 4 extended to sacrum. Sixteen patients had sciatica-like extension of back pain. A difference in SJS between left and right side were observed only in CD patients (1,3± 0,8 e 0,8± 0,9 respectively; p<0,05), but not in UC (1,5± 1,2 vs 1,5± 1,3; p=ns) nor in total IBD patients (1,4± 1 vs 1,2± 1,2; p=ns). Total SJS was higher in UC respect CD, but not significantly (2,9± 2,3 vs 2,1± 1,5; p=ns). Our data confirm the importance of these symptoms in patients with IBD, who need to be carefully investigated also for these aspects.